2018
DOI: 10.5468/ogs.2018.61.1.95
|View full text |Cite|
|
Sign up to set email alerts
|

Pre-implantation genetic diagnosis and pre-implantation genetic screening: two years experience at a single center

Abstract: ObjectiveIndications for preimplantation genetic diagnosis (PGD)/preimplantation genetic screening (PGS) cycles and clinical outcomes were evaluated at CHA Gangnam Medical Center.MethodsThis is retrospective cohort study. All patients (n=336) who went through in vitro fertilization (IVF)-PGD/PGS cycles (n=486) between January 2014 and December 2015 were included in Fertility Center of CHA Gangnam Medical Center. Patients underwent IVF-PGD/PGS with 24-chromosome screening. Patients with euploid embryos had tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…This study represents the largest PGT‐M and PGT‐SR data set reviewing embryo outcomes and pregnancy rates published in North America. Three other studies have analyzed PGT‐M and/or PGT‐SR outcomes at their centers . A recent study in London reviewed 82 couples undergoing PGT for autosomal and sex‐linked conditions and one case of a single gene disorder and chromosome rearrangement .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study represents the largest PGT‐M and PGT‐SR data set reviewing embryo outcomes and pregnancy rates published in North America. Three other studies have analyzed PGT‐M and/or PGT‐SR outcomes at their centers . A recent study in London reviewed 82 couples undergoing PGT for autosomal and sex‐linked conditions and one case of a single gene disorder and chromosome rearrangement .…”
Section: Discussionmentioning
confidence: 99%
“…In another study, Won et al reviewed 116 PGT‐SR cycles for 76 patients at a center in Korea. These authors reported 24 Robertsonian translocations, 60 reciprocal translocations, three inversions, two deletions, four additions, and 23 mosaicisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, these carriers can opt for natural pregnancy along with prenatal diagnosis [ 10 ]. For inversion carriers with asthenospermia, PGD treatment should be recommended [ 19 ]. For inversion carriers with azoospermia, the possible etiology needs further analysis.…”
Section: Discussionmentioning
confidence: 99%